Efficacy and safety of oral panobinostat plus subcutaneous bortezomib and oral dexamethasone in patients with relapsed or relapsed and refractory multiple myeloma (PANORAMA 3): an open-label, randomised, phase 2 study. Issue 1 (January 2021) - Laubach, Jacob P; Schjesvold, Fredrik; Mariz, Mário; Dimopoulos, Meletios A; Lech-Maranda, Ewa; Spicka, Ivan; Hungria, Vania T M; Shelekhova, Tatiana; Abdo, Andre; Jacobasch, Lutz; Polprasert, Chantana; Hájek, Roman; et al.
Summary: Background: Improved therapeutic options are needed for patients with relapsed or relapsed and refractory multiple myeloma. Subcutaneous bortezomib has replaced intravenous bortezomib as it is associated with a more favourable toxicity profile. We investigated the activity and safety of three different dosing regimens of oral panobinostat in combination with subcutaneous bortezomib and oral dexamethasone for this indication. Methods: PANORAMA 3 is an open-label, randomised, phase 2 study being done at 71 sites (hospitals and medical centres) across 21 countries. Patients aged 18 years or older with relapsed or relapsed and refractory multiple myeloma (as per International Myeloma Working Group 2014 criteria), who had received one to four previous lines of therapy (including an immunomodulatory agent), and had an Eastern Cooperative Oncology Group performance status of 2 or lower, were randomly assigned (1:1:1) to receive oral panobinostat 20 mg three times weekly, 20 mg twice weekly, or 10 mg three times weekly, plus subcutaneous bortezomib and oral dexamethasone. All study drugs were administered in 21-day cycles. Randomisation was done by an interactive response technology provider, and stratified by number of previous treatment lines and age. The primary endpoint was overall response rate after up to eight treatment cycles (analysed in all randomly assigned patients by intention to treat). Safety analyses included all patients who received at least one dose of any study drug. No statistical comparisons between groups were planned. This trial is ongoing and registered with ClinicalTrials.gov, NCT02654990 . Findings: Between April 27, 2016, and Jan 17, 2019, 248 patients were randomly assigned (82 to panobinostat 20 mg three times weekly, 83 to panobinostat 20 mg twice weekly, and 83 to 10 mg panobinostat three times weekly). Median duration of follow-up across all treatment groups was 14·7 months (IQR 7·8–24·1). The overall response rate after up to eight treatment cycles was 62·2% (95% CI 50·8–72·7; 51 of 82 patients) for the 20 mg three times weekly group, 65·1% (53·8–75·2; 54 of 83 patients) for the 20 mg twice weekly group, and 50·6% (39·4–61·8; 42 of 83 patients) for the 10 mg three times weekly group. Grade 3–4 adverse events occurred in 71 (91%) of 78 patients in the 20 mg three times weekly group, 69 (83%) of 83 patients in the 20 mg twice weekly group, and 60 (75%) of 80 patients in the 10 mg three times weekly group; the most common (≥20% patients in any group) grade 3–4 adverse events were thrombocytopenia (33 [42%] of 78, 26 [31%] of 83, and 19 [24%] of 83 patients) and neutropenia (18 [23%], 13 [16%], and six [8%]). Serious adverse events occurred in 42 (54%) of 78 patients in the 20 mg three times weekly group, 40 (48%) of 83 patients in the 20 mg twice weekly group, and 35 (44%) of 83 patients in the 10 mg three times weekly group; the most common serious adverse event (≥10% patients in any group) was pneumonia (nine [12%] of 78, ten [12%] of 83, and nine [11%] of 80 patients). There were 14 deaths during the study (five [6%] of 78 patients in the 20 mg three times weekly group, three [4%] of 83 in the 20 mg twice weekly group, and six [8%] of 80 in the 10 mg three times weekly group); none of these deaths was deemed treatment related. Interpretation: The safety profile of panobinostat 20 mg three times weekly was more favourable than in previous trials of this regimen with intravenous bortezomib, suggesting that subcutaneous bortezomib improves the tolerability of the panobinostat plus bortezomib plus dexamethasone regimen. The overall response rate was highest in the 20 mg three times weekly and 20 mg twice weekly groups, with 10 mg three times weekly best tolerated. Funding: Novartis Pharmaceuticals and Secura Bio.